Current Role of Anti-Integrin Therapy in Inflammatory Bowel Disease - Kevin Winston; Hasan Maulahela; Lusiani Lusiani; Raditya Dewangga; Lazuardi G Ilhami (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Inflammatory bowel disease (IBD) is a chronic inflammatory intestinal disorder with multifactorial etiology. Management of IBD is divided into conventional treatment and new treatment with biologic agents. The first biologic agents used for IBD was tumor necrosis factor (TNF)-inhibitor. However, TNF-inhibitor as a biologic agent has several limitations such as low rate of clinical response and systemic immunosuppressive side effects. Anti-integrin is a recently developed biologic agent which selectively inhibits leukocyte trafficking towards site of inflammation. The inhibition is caused by blocking the actions of integrin, a cell adhesion molecules (CAMs) that is necessary for leukocyte trafficking and leukocytes express specific integrin receptors for specific organs. Therefore, use of gut-specific anti-integrin agents in IBD can selectively prevent influx of leukocytes into the intestine to reduce inflammation without reducing immune function in other locations. As a result, gut-specific anti-integrin is hypothesized to have lower risk of infections and lower risk of malignancy than TNF-inhibitor while maintaining high therapeutic benefits, making anti-integrin a promising therapy for IBD in the future.